Work-Related Stress and Teaching Performance of Teachers in Selected School in the Philippines - AURORA SARABIA; LEILA M. COLLANTES (Indonesian Research Journal in Education |IRJE|, 2020)
This study determined the predictor of teaching performance among the components of work-related stress to 210 selected elementary and secondary public teachers in Angeles City. It described the participants’ socio-demographic characteristics, level of work-related stress, and teaching performance, and likewise compared the work-related stress of the participants. The research design used was a descriptive-correlational design with various statistical tools such as descriptive statistics, independent T-Test, and multiple linear regressions. The study revealed that selected elementary and secondary teachers of Angeles City had a moderate work-related stress with the subcomponent demand as highly contributory to the stress. Gender and position were positive predictors of teaching performance where female and teachers with higher teaching position tended to have a higher teaching performance. On the other hand, seminars attended relative to stress and demand which is a sub-component of work-related stress are the negative significant predictors of teaching performance. This implies that teachers who attended seminars related to stress management had higher teaching performance compared to those who did not. This result also established that the higher level of demand, which is a sub-component of stress, can result in lower teaching performance.